Estimating exposures from spray products using robotic simulations - Shin, Mi K; Qian, Hua; Lee, Jee-Eun; Sentis, Luis; Maberti, Silvia I (Annals of work exposures and health, 2023)
Abstract There is an increasing need for exposure data to enable more precise information for risk estimates and improved public health protection. While personal monitoring data are preferred, it is often difficult to collect due to the resources needed to complete a human research study. In this study, we successfully programmed a robotic arm to mimic human use (spraying) of a fabric crafts protector (FCP) and human cleaning (spraying and wiping) of a glass pane with glass cleaner (GC). The robot was then used in place of human subjects to assess inhalation exposures to volatile organic compounds (VOCs) during the use of the FCP and GC. Air sampling data were collected while the robot used the products to estimate personal exposures to VOCs. Average VOC concentrations were 1.57 ppm for FCP spraying and 0.17 ppm for GC spraying and wiping. During FCP spraying, average acetone concentrations were 0.88 ppm and average isopropyl alcohol concentrations were 0.26 ppm. During GC spraying and wiping, average 2-butoxyethanol concentrations were 0.15 ppm. Air sampling data were found to be within the range of data reported in the literature during human use of similar glass cleaning products. No data was found in the literature during use of fabric protector spray products. This study contributes exposure measurement data with detailed contextual information to help characterize inhalation exposures during the use of 2 spray products. In addition, the study offers a systematic, efficient method for generating exposure data which can be used to improve health and safety risk assessments used for public health protection.